Measurements and modelling of airborne plutonium in Subarctic Finland between 1965 and 2011 - Salminen-Paatero, Susanna; Vira, Julius; Paatero, Jussi (2019)
The activity concentrations of 238,239,240 Pu and ,sup>241 Am (for determining its mother nuclide 241 Pu) as well as activity ratios 238 Pu/ 239+240 Pu, 241 Pu/ 239+240 Pu, 239+240 Pu/ 137 Cs, and mass ratio 240 Pu/ 239 Pu were determined from air filter samples collected in Rovaniemi (Finnish Lapland) in 1965–2011. The origin of plutonium in surface air was assessed based on this data from long time series. The most important Pu sources in the surface air of Rovaniemi were atmospheric nuclear weapons testing in 1950’s and 1960’s, later nuclear tests in 1973–1980, and SNAP-9A satellite accident in 1964, whereas the influence from the 1986 Chernobyl accident was only minor. Contrary to the alpha emitting Pu isotopes, 241 Pu from the Fukushima accident in 2011 was detected in Rovaniemi. Dispersion modelling results with the Silam model indicate that Pu contamination in northern Finland due to hypothetical reactor accidents would be negligible in case of a floating reactor at the Shtokmann natural gas field and relatively low in case of an intended nuclear power plant in western Finland.